224k views
1 vote
Standard form for -3x^+ x=13

User Thlgood
by
5.2k points

1 Answer

2 votes

Answer:

to put the equation into standard for we must multiply the terms on the right side of the equation. To multiply these two terms you multiply each individual term in the left parenthesis by each individual term in the right parenthesis.

Explanation:

y

=

(

x

13

)

(

x

12

)

becomes:

y

=

(

x

×

x

)

(

x

×

12

)

(

13

×

x

)

+

(

13

×

12

)

y

=

x

2

12

x

13

x

+

156

We can now combine like terms:

y

=

x

2

+

(

12

13

)

x

+

156

y

=

x

2

+

(

25

)

x

+

156

y

=

x

2

25

x

+

156

User Dan Gallagher
by
5.9k points